Determining the efficacy of 27 commercially available disinfectants against human noroviruses. Issue 2 (February 2021) - Lee, Jae-Woong; Kang, Lae-Hyung; Kim, Min-Kyeong; Kim, Jeong-Soon; Kim, Myung L.; Lee, Sung-Geun; Choi, In-Hye; Park, Chul-Jong; Paik, Soon-Young
Abstract: Background: Recently, monoclonal-antibody–conjugated immunomagnetic separation (IMS) procedure combined with quantitative reverse transcription-polymerase chain reaction (qRT-PCR) has been used for quantifying non-cultivated human noroviruses (HuNoVs). Methods: We examined the efficacy of 27 commercially available disinfectants and a prototype against GII.4 strain HuNoV through the IMS/qRT-PCR assay. Results: The average log reduction in viral titer in vitro varied among the disinfectants. The prototype was the most effective with an average log reduction of 6.86 log. Conclusions: The IMS/RT-qPCR assay is an effective method to evaluate the activities of disinfectants against GII.4 HuNoV in vitro. Further work is needed to enhance the virucidal activity of the prototype disinfectant against more resistant HuNoV strains.